Understanding teachers' multimodal TPACK literacies for supporting VR-based self-directed learning of L1 writing - Jiang, Michael Yi-Chao; Jong, Morris Siu-Yung; Chai, Ching-Sing (Educational Technology ＆ Society, 2024)
Self-directed learning (SDL) is acknowledged as an effective language learning paradigm because learning a language is time-consuming. As language and literacy education is now embracing a more multimodal approach in writing instruction, teachers' multimodal technological, pedagogical, and content knowledge (TPACK) receives growing attention in language education. Based on a VR-supported L1 Chinese writing program, the present study collected and analyzed the VR courseware, lesson plans and student worksheets developed by a group of Chinese language teachers in Hong Kong. A coding scheme regarding multimodal TPACK for SDL was employed to assess the learning activities and to understand teachers' multimodal TPACK literacies in L1 Chinese writing instruction. The findings revealed that teachers were able to use VR to immerse students in an authentic environment to develop students' SDL ability and comprehension of nuanced socioemotional aspects of L1 Chinese writing. Nonetheless, there existed some limitations in the utilization of VR for teaching L1 Chinese writing which might be compensated for by pedagogical design. Moreover, teachers' pedagogical conception revealed their teaching was driven by syllabus requirements and focused on students' completion of writing, which might disregard the process of SDL in pedagogical implementation, and thus the process of collaborative knowledge building might be less developed. This study may contribute to the development of VR-based multimodal TPACK, which enhances multimodal lesson design for self-directed L1 writing.